Identification of Occupational Accident Relations of Shipyard Labour in terms of Individual and Workplace Factors - Muhammad Badrus Zaman; Trika Pitana; Alif Bagas Septianto (International Journal of Marine Engineering Innovation and Research, 2019)
Shipyard is an industry that have major role on trading, shipyard industry leads another industry to triumph, this has been proved in many countries. Factors that are related to workplace accidents in shipyard workers are disturbed when using safety harness while working at height, less knowledge about static electricity, do not take measurements of indoor gas before work, working more than eight hours, constant growing pressure. Precautions include checking safety equipment used to work at height, routinely checking cables, electrical circuits, and electrical equipment, conduct indoor gas measurements, make the worker's shift schedule to eight hours per day and increasing workers to complete the job by finding new employees, short briefing.